Pengaruh Kualitas Layanan Dan Kepercayaan Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan (Studi Pada Hotel Wisata Beach Kabupaten Wakatobi) - Jayadin Jayadin; Murdjani Kamaludin; Juharsah Juharsah (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2023)
The purpose of this study was to examine the effect of service quality and trust on customer loyalty through customer satisfaction (study at Hotel Wisata Beach, Wakatobi Regency). The population in this study are all customers of Hotel Wisata Beach Wakatobi. The number of samples that were set was 60 people or customers, the data from the samples/respondents were analyzed using SmartPLS in order to obtain the results of the causal relationship between the variables developed in the model. The results of the study are as follows; the effect of service quality on customer satisfaction has a path coefficient of 0.452 with a probability level of 0.000 (p <0.05), which means that service quality has a positive and significant effect on customer satisfaction, the effect of trust on customer satisfaction has a path coefficient of 0.331 with a probability level of 0.005 (p < 0.05) which means that trust has a positive and significant effect on customer satisfaction, the effect of service quality on customer loyalty has a path coefficient of 0.219 with a probability level of 0.037 (p < 0.05) which means that service quality has a positive effect and significant on customer loyalty, the effect of trust on customer loyalty has a path coefficient of 0.309 with a probability level of 0.005 (p <0.05), which means that trust has a positive and significant effect on customer loyalty. p customer loyalty has a path coefficient of 0.478 with a probability level of 0.000 (p <0.05) which means that customer satisfaction has a positive and significant effect on loyalty. The effect of service quality on customer loyalty through customer satisfaction has a path coefficient of 0.216 with a probability level of 0.005 ( p <0.05) which means that service quality has a positive and significant effect on customer loyalty through customer satisfaction. The influence of trust on customer loyalty through customer satisfaction has a path coefficient of 0.158 with a probability level of 0.048 (p <0.05) which means that trust has a positive effect and significant effect on customer loyalty through customer satisfaction. The benefit that can be learned from this research is the development of knowledge, especially on the paradigm of structural relationship of the influence of service quality and trust on customer loyalty through customer satisfaction.